Edukasi tentang Kehamilan Risiko Tinggi melalui Kunjungan Rumah di Kelurahan Mojosongo Jebres Surakarta - Anita Dewi Lieskusumastuti; Desti Lestari; Eliza Aulia Fitriani; Catur Setyorini (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Antenatal and postnatal home visiting programs provide significant benefits in improving the health of mothers and babies. Risky pregnancies have the potential to experience life-threatening complications for the mother (85.4%), maternal near misses (13.3%), and maternal death (1.2%). This activity aims to provide education about high-risk pregnancies through home visits. The method is education about high-risk pregnancies using a home visit approach. Location in the Mojosongo Village area, Jebres, Surakarta, Central Java, Indonesia. Activities begin with licensing, preparation, and coordination with the community officer team and study program team, implementation, and evaluation. The results showed that pregnant women had no risk were 56% and high risk were 44%. Risk factors for pregnancy were old age > 35 years, grand multigravida, and hypertension in pregnancy. Mothers are invited to actively read the MCH books, actively discuss, and cooperate. The hope is that pregnant women and their husbands will actively increase their knowledge about healthy pregnancy planning, preparation for childbirth, and newborn babies. Develop an integrated information system for pregnant women that can be accessed by pregnant women. Training program for community officers to improve their ability to assist pregnant women.